2017
DOI: 10.1186/s13568-017-0453-7
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones and induction of plant-stress tolerance and defense genes by seed and foliar inoculation with Azospirillum brasilense cells and metabolites promote maize growth

Abstract: Azospirillum spp. are plant-growth-promoting bacteria used worldwide as inoculants for a variety of crops. Among the beneficial mechanisms associated with Azospirillum inoculation, emphasis has been given to the biological nitrogen fixation process and to the synthesis of phytohormones. In Brazil, the application of inoculants containing A. brasilense strains Ab-V5 and Ab-V6 to cereals is exponentially growing and in this study we investigated the effects of maize inoculation with these two strains applied on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
1
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 75 publications
5
108
1
15
Order By: Relevance
“…Although the exact mechanisms underlying the PGPB effect on wheat development were not evaluated in the present study, it is very likely that the improvement in LCI and N uptake (N foliar concentration and N root and shoot accumulation), reflected in the improved root and shoot dry matter, plant height, spike length, and grain yield by wheat inoculated with A. brasilense, is associated with its well-known ability to promote plant growth [4,13,19,48,49]. Specifically, it was previously demonstrated in draft genome sequences that the strains Ab-V5 and Ab-V6 of A. brasilense, which were tested in the present study, carry similar nif and fix genes that confer their ability to fix atmospheric N [50].…”
Section: Discussionmentioning
confidence: 98%
“…Although the exact mechanisms underlying the PGPB effect on wheat development were not evaluated in the present study, it is very likely that the improvement in LCI and N uptake (N foliar concentration and N root and shoot accumulation), reflected in the improved root and shoot dry matter, plant height, spike length, and grain yield by wheat inoculated with A. brasilense, is associated with its well-known ability to promote plant growth [4,13,19,48,49]. Specifically, it was previously demonstrated in draft genome sequences that the strains Ab-V5 and Ab-V6 of A. brasilense, which were tested in the present study, carry similar nif and fix genes that confer their ability to fix atmospheric N [50].…”
Section: Discussionmentioning
confidence: 98%
“…Application of the metabolites and live bacteria on the leaves of maize equally enhanced plant growth as a result of the phytohormone produced and priming of plant defense genes (Fukami et al 2017; Vacheron et al 2015). …”
Section: Elicitors In the Induction Of Systemic Resistance To Biotic mentioning
confidence: 99%
“…Hungria et al (2010) also obtained increases in corn yield, and depending on the strain of A. brasilense evaluated, the increase in productivity was of the order of 24 to 30%, corresponding to 662 to 823 kg ha -1 . The analysis of results from a large number of field trials with various non-legume crops, conducted worldwide over 20 years, under different soil and weather conditions, has demonstrated that yield increases of up to 30% could be obtained 70% of the time (Fukami et al, 2016;Fukami et al, 2017) in response to inoculation with Azospirillum.…”
Section: Technical Analysis: Corn Grain Yieldmentioning
confidence: 99%
“…Moreover, it is inferred that the application of Azospirillum is also responsible for higher rates of absorption of water and minerals by the plant (Dardanelli et al, 2008) and higher tolerance to abiotic stresses, such as drought and salinity (Zawonski et al, 2011). The relationship between different soil microorganisms and the role of metabolites secreted by them on growth of other surrounding microbial species and plants has been the subject of numerous studies (Marks et al, 2015;Fukami et al, 2016;Fukami et al, 2017), and according to Bashan and de-Bashan (2010), due to the wide array of mechanisms proposed for stimulation of plant growth by Azospirillum spp., probably this bacteria promoves multiple mechanisms that might act either in a cumulative or sequential pattern.…”
Section: Technical Analysis: Corn Grain Yieldmentioning
confidence: 99%
See 1 more Smart Citation